Training on web blog development and management in Gandus Village, Gandus District, Palembang City in the development of knowledge in the field of ICT - Ali Ibrahim; Mira Afrina; Dedeng Zamawi; Yadi Utama (Peneliti Teknologi Teknik Indonesia, 2022)
One way to address the demand for digitally-based information dissemination is through ICT-based training activities. It was a proposal from the Gandus community so that they could share information with the community on a global scale using ICT-like weblogs. The issue was the local community's inability to use and benefit from the internet. Through a weblog or website, the local community was expected to be able to communicate with the outside world about the potential existing in the area in a fair, efficient, and effective manner. With instruction and assistance in creating and administering weblogs in the Gandus community, a weblog-based information system was created and managed by participants to allow for the widespread dissemination of a significant amount of information from the people of the Gandus village.